Penerapan Active Learning dan Penggunaan Media Berbasis Komputer untuk Meningkatkan Prestasi Belajar Siswa pada Pembelajaran IPA - Erni Yuliati (Jurnal Pendidikan Madrasah, 2021)
This study aims to analyze the effectiveness of the application of active learning in increasing interest, attention, and activity, as well as students' learning achievements in science lessons. The subject of the study was a grade VI student of MI Negeri 1 Yogyakarta. This study uses methods of action through the process of incugate. The results showed that the application of active learning through inkuiri method can train students to discover for themselves various concepts learned, foster the ability to think, work, and be scientific and can improve and expand the mastery of skills in the process of acquiring cognitive students.